Feasibility of Preserving No. 5 and No. 6 Lymph Nodes in Gastrectomy of Proximal Gastric Adenocarcinoma: A Retrospective Analysis of 395 Patients - Yang, Xiao; Zheng, Yanan; Feng, Runhua; Zhu, Zhenggang; Yan, Min; Li, Chen (Frontiers in Oncology, 2022)
Objective: The extent of regional lymphadenectomy for proximal gastric cancer (PGC) has remained a controversy and a matter of considerable debate for a long time. We retrospectively analyzed the clinicopathological features to investigate the predictive factors for No.5 and/or No.6 lymph nodes metastases (LNM) and evaluate the feasibility of performing proximal gastrectomy (PG) with preservation of No.5 and/or No.6 lymph nodes for these patients. Method: Patients, who had undergone total gastrectomy plus D2 lymphadenectomy in the department of gastrointestinal surgery, Ruijin Hospital, Shanghai JiaoTong University, School of Medicine from January 2008 to December 2017, were retrospectively collected and analyzed. Results:Among the 395 eligible patients in our study, 34 patients (8.61%) had No.5 and No.6 lymphnode metastasis (LNM). The degree of differentiation, Borrmann classification, vascular or perineural invasion, tumor diameter, depth of invasion, other perigastric LNM were associated with No.5 and/or No.6 LNM. Multivariate analyses showed that tumor diameter ≥ 4 cm, No.4 LNM positive, and No.7, 8, 9 LNM positive were independent risk factors of No.5 and/or No.6 LNM. No.5 and/or No.6 LNM was not observed in the 105 patients, who staged from T1 to T3 and were found to be without independent risk factors. Conclusion: The metastatic rate of No.5 and/or No.6 lymph node of the proximal gastric adenocarcinoma was closely associated with the diameter of the tumor and other perigastric LNM. It is feasible to preserve No.5 and No.6 lymph nodes with proximal gastrectomy for the T1 to T3 patients with lower risk of No.5 and/or No.6 LNM.